1996
DOI: 10.1093/bja/76.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hormonal responses to induced hypotension for middle ear surgery

Abstract: We have investigated in 30 patients the metabolic and hormonal responses to middle ear surgery using induced hypotension to a mean arterial pressure of 55 mm Hg. A standardized anaesthetic technique of propranolol, thiopentone-vecuronium-isoflurane was used in all patients and hypotension induced with sodium nitroprusside, trimetaphan camsylate or additional isoflurane. All patients showed a classic stress response with an increase in circulating blood glucose, cortisol and growth hormone concentrations. Blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
2
16
0
Order By: Relevance
“…Controlled hypotension with either remifentanil, or esmolol, or nitroprusside ensured "good operative conditions". The hemodynamic data for nitroprusside and esmolol are in agreement with those previously reported in middle ear surgery 3,5,7 and in other surgery. 11,[20][21][22] Advantages and disadvantages of sodium nitroprusside for deliberate hypotension which include potency and short duration of action, and reflex tachycardia, tachyphylaxis, rebound hypertension, potential for cyanide toxicity, have been discussed several previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Controlled hypotension with either remifentanil, or esmolol, or nitroprusside ensured "good operative conditions". The hemodynamic data for nitroprusside and esmolol are in agreement with those previously reported in middle ear surgery 3,5,7 and in other surgery. 11,[20][21][22] Advantages and disadvantages of sodium nitroprusside for deliberate hypotension which include potency and short duration of action, and reflex tachycardia, tachyphylaxis, rebound hypertension, potential for cyanide toxicity, have been discussed several previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…Lack of relationships between hypotension, heart rate and middle ear blood flow observed in the present study and in a previous one 4 could be explained by autoregulation, 2 8 altered baroreceptor activation, 3 0 enhanced sympathetic nerve activity 6 and/or renin angiotensin secretion. 5 Reduction of heart rate and hypotension with remifentanil and esmolol could account for the impairment of baroreflex regulatory mechanisms caused by propofol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Tranexamic acid also has been used topically for control of bleeding in FESS. 23 Ethamsylate is haemostatic drug used for control of dysfunctional uterine bleeding 8,9 and periventricular haemorrhage in children. 24 Oral route has been used to control bleeding in dacryocystorhinostomy surgery and for control of epistaxis.…”
Section: Role Of Vasodilatorsmentioning
confidence: 99%
“…23,25 Gelatin thrombin matrix: It stops bleeding on an average of 2 minutes. 26 Some studies reported its adverse effect, 27,28,29 but one study evaluated its efficiency without complications.…”
Section: Surgical Considerationsmentioning
confidence: 99%